Development of Basic Geology Mobile Learning Based on Android Indonesia Geodiversity Area - Riswadinata, Indra; Prasetiyo, Tri Kukuh; Diniyati, Nurul (JURNAL GEOGRAFI, 2024)
Basic Geology is a prior knowledge that needs to be supported by a flexible learning environment through the use of mobile technology. Through the supports of mobile technology, students will gain freedom of access because they can be used anytime and anywhere. The progress and speed of technological development, the ease and practicality of using smartphone devices are the potential, opportunities and challenges for presenting mobile technology in learning. The presence of generation Z who are already familiar with technology has reinforced the need to utilize technology to accommodate them in learning better. The aim of this development research is to produce a learning product in the form of a Basic Geology mobile learning application to support learning anywhere and anytime and to determine the feasibility of the product in terms of media and materials, as well as responses from users. This research uses the Lee & Owens model in developing mobile learning applications. Data was collected using a questionnaire filled out by media experts, material experts and service users in the Indonesian Geodiversity Area. The results of this research are (1) user needs for mobile learning to support Basic Geology learning by providing learning resources and building learning communities, (2) producing Basic Geology mobile learning products, (3) results of feasibility tests by media experts, material experts and Individual, small group and field trials show that mobile learning is suitable for use in learning.Keywords: geodiversity; basic geology; mobile learning